(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The article discusses the features of ensuring the economic security of industrial enterprises and the factors influencing them, principles, problems associated with ensuring the economic security of industrial enterprises, proposes conceptual directions for ensuring the economic security of an enterprise, and provides conclusions and recommendations for ensuring the economic security of industrial enterprises.